PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA MENGGUNAKAN METODE GAME BASED LEARNING BERBANTUAN MEDIA PAPAN JURANG SISWA SEKOLAH DASAR - Najla Sulthanah; Fadhilaturrahmi; Indriyanto; Nurhaswinda; Iis Aprinawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the mathematical concept understanding of Grade II students at UPT SD Negeri 005 Binuang through the implementation of the Game-Based Learning (GBL) method assisted by the Papan Jurang media. The research employed a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of two meetings. Each cycle included the stages of planning, implementation, observation, and reflection. The subjects of this study were the Grade II students of UPT SD Negeri 005 Binuang, totaling 20 students, comprising 7 boys and 13 girls. Data collection techniques used in this study included observation, tests, and documentation, while the research instruments consisted of observation sheets and written tests. The data were analyzed using both qualitative and quantitative methods. The results showed that the classical completeness percentage of students increased from 38.50% in Cycle I Meeting I to 53.85% in Cycle I Meeting II, then rose to 69.23% in Cycle II Meeting I, and reached 92.31% in Cycle II Meeting II. Therefore, it can be concluded that the implementation of the Game-Based Learning method assisted by the Papan Jurang media is effective in enhancing students’ understanding of mathematical concepts.